MODIFYING ASSESSMENT FOR THE ADVANCEMENT OF FAMILY LAW THEORIES AND PRACTICES - Anwar, Wirani Aisiyah; Wahyu, A. Rio Makkulau; Mukhlas, Oyo Sunaryo; Khosyiah, Si’ah (Jurnal Al-Dustur, 2024)
Family law primarily refers to the legal rules that regulate relationships within the family, which can derive from either blood relations or the act of marriage. The purpose of this article is to analyze the concept and the norm of altering Islamic family law in Indonesia. To examine the subject of altering Islamic family law in Indonesia, a qualitative methodology backed by literature can be used. A combination with descriptive normative approach entails researching legal documents related to Islamic families in Indonesia, selecting some contentious family law cases and analyzing their impact on the legal system, and interviewing Islamic legal experts, human rights activists, or family members involved in specific legal cases. The results of the study underline the significance of family bonds in influencing problems such as parental and filial rights, inheritance laws, along with custody and guardianship. Essentially, family law has its foundation on two sources: written and unwritten regulations. Written sources include a wide range of legal topics, including law, jurisprudence, and treaties. Unwritten sources, on the other hand, refer to legal ideas that emerge and shape themselves within the context of cultural life.